Work stress and health risk behavior - Siegrist, Johannes; Rödel, Andreas (Scandinavian Journal of Work, Environment & Health, 2006)
This contribution discusses current knowledge of associations between psychosocial stress at work and health risk behavior, in particular cigarette smoking, alcohol consumption and overweight, by reviewing findings from major studies in the field published between 1989 and 2006. Psychosocial stress at work is measured by the demand–control model and the effort–reward imbalance model. Health risk behavior was analyzed in the broader context of a health-related Western lifestyle with socially and economically patterned practices of consumption. Overall, the review, based on 46 studies, only modestly supports the hypothesis of a consistent association between work stress and health risk behavior. The relatively strongest relationships have been found with regard to heavy alcohol consumption among men, overweight, and the co-manifestation of several risks. Suggestions for further research are given, and the need to reduce stressful experience in the framework of worksite health promotion programs is emphasized.
Keywords: alcohol consumption; cigarette smoking; demand–control model; effort–reward imbalance; effort–reward imbalance model; ERI; health risk behavior; health-related lifestyle; overweight; review; work stress